1987
DOI: 10.1530/acta.0.1150084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sham-feeding on glucose tolerance and insulin secretion

Abstract: Glucose, 25 g, was infused iv with or without sham-feeding in seven normal males. Sham-feeding improved glucose tolerance, incremental area of blood glucose being 63% (P < 0.05) of that during iv glucose without sham-feeding. The actual insulin secretion evaluated from the total area under the C-peptide and insulin curves did not differ during iv glucose with or without sham-feeding. These results suggest that the cephalic-vagal reflex improves glucose tolerance during iv glucose, independent of changes in \g=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 13 publications
(22 reference statements)
2
18
0
Order By: Relevance
“…For example, intragastric administration of nutrients that bypasses the oropharyngeal cavity (Proietto et al, 1987;Steffens, 1976) and the transplantation of islets as a means of denervation (Berthoud et al, 1980), result in elevated levels of both insulin and glucose. Human experiments support these findings (Bryde-Andersen et al, 1995;Calles-Escandon, 1987;Lorentzen et al, 1987). We found that when sham feeding was paired with the intragastric administration of glucose, postprandial glucose levels were reduced by 33% compared with intragastric glucose alone (Teff & Engelman, 1996a) (Fig.…”
Section: Physiological Significance Of the Cephalic Physiological Sigsupporting
confidence: 62%
“…For example, intragastric administration of nutrients that bypasses the oropharyngeal cavity (Proietto et al, 1987;Steffens, 1976) and the transplantation of islets as a means of denervation (Berthoud et al, 1980), result in elevated levels of both insulin and glucose. Human experiments support these findings (Bryde-Andersen et al, 1995;Calles-Escandon, 1987;Lorentzen et al, 1987). We found that when sham feeding was paired with the intragastric administration of glucose, postprandial glucose levels were reduced by 33% compared with intragastric glucose alone (Teff & Engelman, 1996a) (Fig.…”
Section: Physiological Significance Of the Cephalic Physiological Sigsupporting
confidence: 62%
“…Although causality has not been established, the sensory signal likely modulates the overall response, so the organism is not threatened by marked hypoor hyperglycemia after an ingestive event. Blocking the CPIR leads to greater peak postprandial plasma glucose concentrations and a prolonged elevation of circulating glucose (Calles-Escandon & Robbins, 1987;Lorentzen, Madsbad, Kehlet, & Tronier, 1987;Steffens, 1976). Many other examples of cephalic phase responses to oral stimulation could be cited such as bitterness evoking CCK release with implications for gastric emptying and appetite (Jeon, Seo, & Osborne, 2011;Sternini, 2007), saltiness moderating renal sodium clearance and possibly blood pressure levels (Akaishi, Shingai, Miyaoka, & Homma, 1991), or fat taste influencing circulating triglyceride concentrations and cardiovascular disease risk (Mattes, 1996b(Mattes, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Incremental areas of plasma insulin, plasma C-peptide, and insulin secretion rates were not significantly influenced by sham feeding. We conclude that sham feeding by the sight and smell of food improves glucose tolerance in normal subjects without alteration in insulin secretion.Modified sham feeding performed with the chew and spit technique may improve intravenous glucose toler ance in normal subjects because of an earlier and higher insulin peak [1]. In the study by Lorentzen et al…”
mentioning
confidence: 99%
“…In the study by Lorentzen et al [1] the modified sham feeding was performed without any con trol of whether any food reached the stomach. The early cephalic insulin release has been well described in several studies, in detail by Teff et al [2] in normal weight males in relation to a meal.…”
mentioning
confidence: 99%